Galectin-3 binds Neisseria meningitidis and increases interaction with phagocytic cells - Quattroni, P; Li, Y; Lucchesi, D; Lucas, S; Hood, D; Herrmann, M; Gabius, H; Tang, C; Exley, R (2012)
Galectin-3 is expressed and secreted by immune cells and has been implicated in multiple aspects of the inflammatory response. It is a glycan binding protein which can exert its functions within cells or exogenously by binding cell surface ligands, acting as a molecular bridge or activating signalling pathways. In addition, this lectin has been shown to bind to microorganisms. In this study we investigated the interaction between galectin-3 and Neisseria meningitidis, an important extracellular human pathogen, which is a leading cause of septicaemia and meningitis. Immunohistochemical analysis indicated that galectin-3 is expressed during meningococcal disease and colocalizes with bacterial colonies in infected tissues from patients. We show that galectin-3 binds to N.meningitidis and we demonstrate that this interaction requiresfull-length, intact lipopolysaccharide molecules. We found that neither exogenous nor endogenous galectin-3 contributes to phagocytosis of N.meningitidis; instead exogenous galectin-3 increases adhesion to monocytes and macrophages but not epithelial cells. Finally we used galectin-3 deficient (Gal-3-/-) mice to evaluate the contribution of galectin-3 to meningococcal bacteraemia. We found that Gal-3-/- mice had significantly lower levels of bacteraemia compared with wild-type mice after challenge with live bacteria, indicating that galectin-3 confers an advantage to N. meningitidis during systemic infection. © 2012 Blackwell Publishing Ltd.